Stationary Rossby waves dominate subduction of anthropogenic carbon in the Southern Ocean. Issue 1 (December 2017) - Langlais, C.; Lenton, A.; Matear, R.; Monselesan, D.; Legresy, B.; Cougnon, E.; Rintoul, S.
Abstract The Southern Ocean has taken up more than 40% of the total anthropogenic carbon (Cant ) stored in the oceans since the preindustrial era, mainly in subantarctic mode and intermediate waters (SAMW-AAIW). However, the physical mechanisms responsible for the transfer of Cant into the ocean interior remain poorly understood. Here, we use high resolution (1/10°) ocean simulations to investigate these mechanisms at the SAMW-AAIW subduction hotspots. Mesoscale Stationary Rossby Waves (SRWs), generated where the Antarctic Circumpolar Current interacts with topography, make the dominant contribution to the Cant transfer in SAMW-AAIW in the Indian and Pacific sectors (66% and 95% respectively). Eddy-resolving simulations reproduce the observed Cant sequestration in these layers, while lower spatial resolution models, that do not reproduce SRWs, underestimate the inventory of Cant in these layers by 40% and overestimate the storage in denser layers. A key implication is that climate model simulations, that lack sufficient resolution to represent sequestration by SRWs, are therefore likely to overestimate the residence time of Cant in the ocean, with implications for simulated rates of climate change.